Technology for Working with Graphic Programs - Shirinov Feruzjon Shuxratovich (Zien Journals, 2022)
This article provides information about working with graphic programs on a computer, their types and capabilities. Some problems encountered in working with graphic programs are discussed.
Keywords: Computer graphics; animation tools; animation programs; Adobe Illustrator